1980
DOI: 10.1083/jcb.84.2.430
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vesicular stomatitis virus infection by spike glycoprotein. Evidence for an intracellular, G protein-requiring step.

Abstract: In an assay measuring virus-directed RNA synthesis, infection of BHK cells by a standard test dose of vesicular stomatitis virus (VSV) was inhibited by ultraviolet light-irradiated wt VSV and by is 045, one of a number of thermolabile, temperature-sensitive G protein mutants of VSV . After heat treatment for 1 h at 45°C, the thermolabile mutants were no longer able to inhibit the VSV infection . In contrast, the thermolabile M protein mutant is G31 and the nonthermolabile G protein mutant is 044 could still in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 18 publications
4
48
1
Order By: Relevance
“…The internalization of VSV thus occurred rapidly and synchronously. Why only one-third of the virus was internalized is not clear, but the inefficient internalization was consistent with previous observations in MDCK and BHK-21 cells (41,50).…”
Section: Kinetics Of Internalization and Acid Activationsupporting
confidence: 79%
See 1 more Smart Citation
“…The internalization of VSV thus occurred rapidly and synchronously. Why only one-third of the virus was internalized is not clear, but the inefficient internalization was consistent with previous observations in MDCK and BHK-21 cells (41,50).…”
Section: Kinetics Of Internalization and Acid Activationsupporting
confidence: 79%
“…VSV binding to the cell surface was quite inefficient and sensitive to external factors, such as pH and cell type (41,50). Internalization was also relatively inefficient, with only onethird of surface-bound virus particles entering the cell.…”
Section: Discussionmentioning
confidence: 97%
“…Internalization of virus particles by endocytosis is accomplished by the uncoating of viral nucleocapsids after fusion with primary lysosomes (Helenius et al, 1980;Matlin et al, 1982). A low pH in these organelles seems to trigger a fusion between viral envelopes and lysosomal membranes (Helenius et al, 1980;White et al, 1980), whereas the increase of intralysosomal pH with lysosomotropic agents such as NH,C1 (Ohkuma & Poole, 1978) or chloroquine (Miller & Lenard, 1980) was shown to block the release of the viral genome into the cytoplasm (Matlin et al, 1982). Mallucci (1966) reported a differential effect of chloroquine on MHV3 replication in mouse macrophages, which was thought to be due to enzymes escaping from the lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of chloroquine, a lysosomotropic agent (Ohkuma & Poole, 1978), was also examined. A previous report using chloroquine during VSV infection suggested that lysosomes were required for uncoating of the virus, and that only 50% of the viral RNA was made when chloroquine was added 1.5 h after infection (Miller & Lenard, 1980). Therefore, we added chloroquine to ts G31-infected N-18 cells 2 h after infection to allow initiation of infection but to block subsequent lysosomal enzyme activity.…”
Section: Effect Of Various Metabolic Inhibitors On Ts G31-induced Cytmentioning
confidence: 99%